2021
DOI: 10.3390/cancers13102490
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinogen Cadmium Activates Lysine 63 (K63)-Linked Ubiquitin-Dependent Signaling and Inhibits Selective Autophagy

Abstract: Signaling, proliferation, and inflammation are dependent on K63-linked ubiquitination—conjugation of a chain of ubiquitin molecules linked via lysine 63. However, very little information is currently available about how K63-linked ubiquitination is subverted in cancer. The present study provides, for the first time, evidence that cadmium (Cd), a widespread environmental carcinogen, is a potent activator of K63-linked ubiquitination, independently of oxidative damage, activation of ubiquitin ligase, or proteaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown that polyubiquitin chains are recognition signals for cargo receptors ( 23 ). Unlike the proteasomal pathway, where K48-linked ubiquitin chains serve as a major degradation signal, we and other groups have shown that polyubiquitin chains of other lineages can also be recognized by cargo receptors for autophagic degradation ( 9 , 11 , 31 33 ). K63-linked ubiquitination was originally reported as a nondegradation signal that mediated the activation of signaling cascades in innate immunity ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies have shown that polyubiquitin chains are recognition signals for cargo receptors ( 23 ). Unlike the proteasomal pathway, where K48-linked ubiquitin chains serve as a major degradation signal, we and other groups have shown that polyubiquitin chains of other lineages can also be recognized by cargo receptors for autophagic degradation ( 9 , 11 , 31 33 ). K63-linked ubiquitination was originally reported as a nondegradation signal that mediated the activation of signaling cascades in innate immunity ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 90%
“…We observed that cadmium exposure induced accumulation of ubiquitinated proteins and aggresome formation in HK-2 cells, RPTECs, and RPTEC/TERT1, another human proximal tubular cell line (data not shown). It has been reported that cadmium exposure does not affect proteasome activity 51 , 52 . Cadmium exposure induces protein misfolding and aggregation by binding to the thiol groups of cysteine residues in cells 37 .…”
Section: Discussionmentioning
confidence: 96%
“…The alterations of phosphatidylinositol phosphorylation (three genes) and ubiquitination (two genes) are interesting, since both are critical cellular regulation pathways implicated in PAH-induced carcinogenicity [86][87][88][89][90]. Considering the observed developmental delays in sensitive embryos exposed to polluted sediments (Fig.…”
Section: Metabolic Gene Expression Of Sensitive Resistant and Crossed...mentioning
confidence: 99%